2014
DOI: 10.1021/pr500550t
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Proteome Signatures in Early Bovine Embryo Development

Abstract: Development of early embryonic stages before activation of the embryonic genome depends on sufficiently stored products of the maternal genome, adequate recruitment and degradation of mRNAs, as well as activation, deactivation, and relocation of proteins. By application of an isobaric tagging for relative and absolute quantification (iTRAQ)-based approach, the proteomes of bovine embryos at the zygote and 2-cell and 4-cell stage with MII oocytes as a reference were quantitatively analyzed. Of 1072 quantified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 91 publications
3
45
0
Order By: Relevance
“…It is further suggested that these piRNAs are kept relatively unstable by post-transcriptional 3’-adenylation and are likely to be a signal for degradation possibly after activation of the embryonic genome 13 . Our qPCR data of expression of PIWIL3, TDRKH and PNLDC1 mRNA indicate that the piRNA biogenesis complex in bovine embryos is mainly functional before the morula stage, also in agreement with a coordinated decrease in TDRKH and PNLDC1 levels during embryonic development detected previously 32 . While other PIWI proteins have been studied rigorously in lower model organisms, this study is the first to provide evidence in oocytes of mammals that piRNAs are present in a complex comprising both PIWIL3, TDRKH and PNLDC1.…”
Section: Discussionsupporting
confidence: 90%
“…It is further suggested that these piRNAs are kept relatively unstable by post-transcriptional 3’-adenylation and are likely to be a signal for degradation possibly after activation of the embryonic genome 13 . Our qPCR data of expression of PIWIL3, TDRKH and PNLDC1 mRNA indicate that the piRNA biogenesis complex in bovine embryos is mainly functional before the morula stage, also in agreement with a coordinated decrease in TDRKH and PNLDC1 levels during embryonic development detected previously 32 . While other PIWI proteins have been studied rigorously in lower model organisms, this study is the first to provide evidence in oocytes of mammals that piRNAs are present in a complex comprising both PIWIL3, TDRKH and PNLDC1.…”
Section: Discussionsupporting
confidence: 90%
“…The lysates were sonicated five times for 2 s each at 30% amplitude. Then the sonicated lysates were centrifuged for 30 min at 4°C at 12000 g and obtained the supernatants (Deutsch et al, 2014). After quantitative assay by the Bradford method (Bradford Protein Assay kit) (Deutsch et al, 2014), 60 μg protein was reduced, alkylated and trypsin digested.…”
Section: Methodsmentioning
confidence: 99%
“…Then the sonicated lysates were centrifuged for 30 min at 4°C at 12000 g and obtained the supernatants (Deutsch et al, 2014). After quantitative assay by the Bradford method (Bradford Protein Assay kit) (Deutsch et al, 2014), 60 μg protein was reduced, alkylated and trypsin digested. Each sample was separated by a high performance liquid chromatography (HPLC) system (Ultimate 3000, Thermo Scientific), and analyzed by mass spectrometry (Q-Exactive HF, Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, increasing the input amount to 4,000-8,000 embryos per sample proved sufficient to distinguish ~5,000 proteins during mouse development from 1-cell stage to blastocyst (Gao et al 2017). Bovine oocytes and embryos are larger, and by analyzing 100 of them (Deutsch et al 2014;Demant et al 2015), ~1,000 to 1,500 proteins were detected. While based on different MS technologies, all these studies shared high numbers of oocytes or embryos, far greater than the single Xenopus or the few Drosophila oocytes that were sufficient to detect ~5,000 proteins (Kronja et al 2014;Smits et al 2014;Sun et al 2014;Casas-Vila et al 2017).…”
Section: Introductionmentioning
confidence: 99%